2021
DOI: 10.1002/cpp.2659
|View full text |Cite
|
Sign up to set email alerts
|

Parental separation or divorce and adulthood attachment: The mediating role of the Abandonment schema

Abstract: This study investigated whether the Abandonment schema mediates the relationship between a history of parental separation or divorce and attachment styles in adulthood. Participants (N = 426; M age = 30.78 years) completed online measures, using Qualtrics. Results demonstrated that a history of parental separation or divorce was positively associated with anxious and avoidant attachment styles in adulthood.Mediation analyses revealed that the Abandonment schema mediated these relationships (p < 0.001). This su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…Furthermore, the Disconnection/Rejection dimension of EMS is closely related not only to feelings of abandonment but also to emotional deprivation and feelings of guilt and shame, which, as mentioned, are more frequent in female gamblers (van Wijk-Herbrink et al, 2018 ). In turn, previous evidence suggests that disconnection/rejection is related to both internalising (i.e., depression) and externalising behavioural problems (i.e., GD), and that coping responses mediate these effects (D'Rozario & Pilkington, 2022 ; van Wijk-Herbrink et al, 2018 ). However, the literature exploring GD and EMS is still very scarce, and little is known about possible sex differences.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, the Disconnection/Rejection dimension of EMS is closely related not only to feelings of abandonment but also to emotional deprivation and feelings of guilt and shame, which, as mentioned, are more frequent in female gamblers (van Wijk-Herbrink et al, 2018 ). In turn, previous evidence suggests that disconnection/rejection is related to both internalising (i.e., depression) and externalising behavioural problems (i.e., GD), and that coping responses mediate these effects (D'Rozario & Pilkington, 2022 ; van Wijk-Herbrink et al, 2018 ). However, the literature exploring GD and EMS is still very scarce, and little is known about possible sex differences.…”
Section: Introductionmentioning
confidence: 97%
“…Specifically, we analyzed how coparental respect and cooperation, interparental conflict, positive parenting strategies, and both parents’ emotional state and instability in the post-divorce period are associated with children’s attachment representations during young adulthood. Even though parental divorce or separation might be positively associated with higher attachment-related anxiety and avoidance in adulthood through the development of negative schemas about intimate relationships [ 15 ], changes in parent–child relationships derived from the stress of divorce might also lead to more insecure intimate relationships in young adulthood (17).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, relationship disruptions in the family of origin during childhood might influence the ways in which young adults approach romantic relationships and their mental representations regarding these relationships [ 14 ]. That is, parental divorce or separation might lead to the development of maladaptive schemas about intimate relationships, such as negative expectations towards being abandoned by others, which in turn has been positively associated with anxious and avoidant attachment styles in adult children [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Parents remain key social models for their children (Kärtner et al, 2021). Children learn about marital relationships by observing parents navigate marital difficulties (Alder et al, 2018; D'Rozario & Pilkington, 2022; Gager et al, 2016), and children reflect parental attitudes toward marriage (Willoughby et al, 2012). Offspring who perceived that their parents had low marital satisfaction were less likely to marry and more supportive of divorce (X. Li, 2014).…”
Section: Figurementioning
confidence: 99%
“…Research has shown that parental divorce has negative links with offspring's attitudes toward marriage (Boyer-Pennington et al, 2018). This could be, in part, because parental divorce connects with anxious and avoidant attachment styles (D'Rozario & Pilkington, 2022). Even if parents' marriages remain intact, conflict between parents links to an increased likelihood of offspring's cohabiting dissolution or divorce (Gager et al, 2016).…”
Section: Introductionmentioning
confidence: 99%